Myelodysplastic syndrome diagnosed by genetic testing for hereditary cancer: a case report - Sarah Ridd; Larissa Peck; Aniket Bankar; George S. Charames; Jordan Lerner-Ellis; Radhika Mahajan; Peter J. B. Sabatini; Andrew Wong; Janet Malcolmson; Raymond H. Kim (npj Genomic Medicine)
Abstract Genetic testing for solid tumor syndromes typically uses peripheral blood leukocytes (PBL) as the source of germline DNA. This approach has shortcomings in certain situations, such as somatic mosaicism and hematologic malignancies. Here we describe a case where germline genetic testing on PBL revealed an unsuspected diagnosis of myelodysplastic syndrome (MDS). A 68-year-old male with a history of three solid tumors and a significant family history of cancer underwent germline genetic testing with a 76-gene hereditary cancer panel. Initial testing using PBL revealed deletions of the entire APC and CTNNA1 genes, suggestive of a contiguous deletion of chromosome 5 (del(5q)). Subsequent testing on cultured fibroblasts was negative, indicating the deletions were somatic. Bone marrow analysis confirmed the presence of del(5q) and a diagnosis of MDS. This case demonstrates the potential to uncover hematologic disorders through hereditary cancer genetic testing, emphasizing the importance of careful results interpretation, multidisciplinary follow-up, and DNA source selection.